2015
DOI: 10.4274/jus.2015.427
|View full text |Cite
|
Sign up to set email alerts
|

Pain Control and Its Relationship with Histopathological Outcome in TRUS-Guided Prostate Needle Biopsy: A Prospective Non-Randomized Trial

Abstract: What's known on the subject? and What does the study add? ÖZET objective Transrectal ultrasound-guided prostate biopsy (TRUS-Bx) is a standard diagnostic modality for detecting prostate cancer (PCa). Pain during biopsy is the most important problem that still needs a solution. The purpose of this study was to compare 3 pain control techniques and to investigate the relationship between the level of pain and histopathological findings. Materials and Methods 139 patients underwent prostate biopsy utilizing 3 ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Carbocaine causes less vasodilatation and less absorption and has a longer duration of action and may thus be more effective than the lidocaine used in our study. Demir et al reported a higher mean pain score of 8.2 in the intra-rectal lidocaine gel arm of their study which compared three different anaesthetic techniques for prostate biopsy [23]. However, the patients were not randomized into groups in their study.…”
Section: Discussionmentioning
confidence: 98%
“…Carbocaine causes less vasodilatation and less absorption and has a longer duration of action and may thus be more effective than the lidocaine used in our study. Demir et al reported a higher mean pain score of 8.2 in the intra-rectal lidocaine gel arm of their study which compared three different anaesthetic techniques for prostate biopsy [23]. However, the patients were not randomized into groups in their study.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, Demir et al [19] also investigated the correlation between pain control method and pathological diagnosis. Findings in their study revealed anaesthesia type influences pain felt during prostate biopsy in relation to the histopathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%